Using the Uganda Demographic and Health Surveys from 2011 and 2016 to assess changes in Saving Mothers, Giving Life intervention districts - Lindsay Mallick; Trinadh Dontamsetti; Thomas Pullum; Julia Fleuret (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Launched in 2012 in Uganda and Zambia, *Saving Mothers, Giving Life* (SMGL) was a five-year initiative that aimed to improve access to and use of maternal and newborn health care services, as well as strengthen the quality of these services. # Aim This study compared the change in coverage of eight related maternal and child health (MCH) indicators between districts included in the SMGL initiative with the change in selected control areas. These indicators included four or more (4+) antenatal care (ANC) visits; two components of ANC including urine sample taken and blood pressure (BP) measured; postnatal care (PNC) by a skilled provider for the mother; and PNC by a skilled provider for the baby. For births in the preceding three years, we examined facility delivery, delivery with a skilled birth attendant (SBA), and Cesarean section (C-section delivery). # Methods The analysis used data from two Demographic and Health Surveys (DHS) conducted in Uganda, one immediately preceding the initiative (2011) and another in the final year of the initiative (2016). We employed a difference-in-differences analysis to estimate the significance of the difference in the change between the treatment and three different control areas for each indicator. Control areas one and two comprised accumulative districts immediately surrounding the treatment area. The third control area included all districts in the country outside of the treatment area. # Results The results revealed that while respondents and their children in both the SMGL and control areas demonstrated significant improvements in MCH indicators between 2011 and 2016, the gains were largely not significantly different between the treatment and control areas, with the exception of two indicators: blood pressure measurement among women with ANC and births delivered by cesarean section. # Conclusions Although the districts hosting the SMGL initiative did not exhibit improvements greater than those of the control areas, the analysis may be limited by the small sample sizes. National progress in Uganda is laudable; however, results of the difference-in-difference analysis should be interpreted with caution.